Teaching listening comprehension - Penny Ur (Cambridge Univ, 1984)
The book is about developing listening comprehension skills in the language classroom. In Part One, the book defines the characteristics of real-life listening, analyses the problems encountered by language learners, and discusses the considerations involved in planning successful classroom listening practice. Part Two ranges the activities in level from elementary to advanced and illustrates techniques appropriate for both adults and children